EMPLOYEES’ RESISTANCE TO CHANGE DURING POST-MERGER INTEGRATION IN SERVICES ORGANISATIONS: Received: 05th December 2023; Revised: 05th January 2024, 10th January 2024; Accepted: 21st February 2024 - Sharma, Yashasvi; Seetharaman, A.; Maddulety, K. (PEOPLE: International Journal of Social Sciences, 2024)
Mergers and acquisitions are an important strategic option for a corporation to drive higher growth and profitability. Despite significant investments being made in mergers and acquisitions, past experiences indicate that many mergers and acquisitions fail. The failure is often attributed to employees’ resistance to change. Factors, such as organisation change, culture, leadership, trust, and communication, among others, lead to employees’ resistance to change. This issue has a significant impact on service organisations since human capital is their key source of competitive advantage. The purpose of this study is to determine factors influencing employees’ resistance to change during the post-merger integration. This paper synthesises findings from a systemised literature review of ‘peer-reviewed’ research papers, published from November 2020 to November 2023, in ProQuest and EBSCOhost databases with keywords ‘employees’ resistance to change’ and ‘post-merger integration’. The findings establish strategies managers could adopt such as creating a continuous learning environment, recognition of the existence of subcultures within a culture, greater involvement of middle managers in the integration phase, devising an appropriate reward plan for early adopters, and focusing on the pace of changes. The study outcomes will help organisations in designing effective post-merger integration programmes leading to efficient use of capital.